Analisis Pengaruh Perilaku Hedonic Shopping, Display Product, Price Discount, Dan Positive Emotion Terhadap Keputusan Pembelian Impulsif(Survei Di Centro Departement Store Solo Paragon) - Susilo, Apriyan; , Imronudin, S.E,M.Si,Ph.D (2017)
The purpose of this research are: 1) To examine the effect of hedonic shopping behavior against impulsive buying decisions. 2) To examine the effect of display product against impulsive buying decisions. 3) To examine the effect of price discount on purchase decisions impulsively. 4) To test the effects of positive emotion on impulsive buying decisions. The population in this research are all consumers who make purchases in Centro Department Store Solo Paragon. The samples in the research using a convenience sampling, the samples in this research are the consumers of who already make a purchase of products in Centro Department Store Solo Paragon. Based on this research variable hedonic shopping behaviour have a significant influence on impulsive buying decision. Variable display product have a significant influence on impulsive buying decision. Variable price discount have a significant influence on impulsive buying decision. Variable positive emotion have a significant influence on impulsive buying decision.